Investigation of Normal Modes in Microstrip Multiconductor Line Using the MoM - Mikučionis, Š.; Urbanavičius, V. (Elektronika ir Elektrotechnika, 2010)
The technique of investigation of normal waves excitation and propagation conditions in a microstrip multiconductor line (MMCL) in the quasi-TEM approximation is submitted in this article. The method of moments is used for calculation of capacitance matrixes of the MMCL and parameters of normal waves propagation. Values of voltages, which excite normal waves in the MMCL, are found calculating eigenvalues of relative effective dielectric permittivity vector. Using the software created by authors, and analyzing the three-conductor MMCL, good conformity of the parameters calculated by the proposed technique and parameters submitted in publications of other researchers is shown. Characteristics of normal waves excitation and conditions of their propagation in the fourconductor MMCL from its design parameters are investigated also. Ill. 3, bibl. 17, tabl. 2 (in English; abstracts in English, Russian and Lithuanian).